Understanding the relationship between chronic pain and emotional disorders - Tadjibaev, Arman (2021)
Although frequent coexistence of chronic pain and emotional disorders is well documented, exact mechanisms of comorbidity are not fully understood. The overarching aim of this thesis was to advance our knowledge of the mechanisms that link chronic pain and emotional disorders.